Bioaccumulation of chlorophacinone in strains of rats resistant to anticoagulants. Issue 3 (29th October 2012) - Vein, Julie; Vey, Danièle; Fourel, Isabelle; Berny, Philippe
Abstract BACKGROUND: Anticoagulants are the only available compounds in the EU to control rat populations. Resistance to anticoagulant rodenticides (antivitamin K or AVK) is described and widespread across Europe. The present objective was to determine whether resistance was associated with an increased potential for bioaccumulation of AVK in the liver. Rats were selected from three major resistant genetically identified strains across Europe: Y139C (Germany), Y139F (France) and L120Q (United Kingdom). The rats were housed in individual cages and fed chlorophacinone wheat bait (50 mg kg−1). Animals were assigned to groups for euthanasia either on day 1, 4, 9 or 14 (resistant rats) or on days 1 and 4 (susceptible rats). RESULTS: Chlorophacinone accumulated from day 1 to day 4 in all strains (maximum 160 µg liver−1) and remained stable thereafter. There was no significant difference between strains. Extensive metabolism of chlorophacinone was also found, and was similar (in nature and proportion of metabolites) across strains (3 OH‐metabolites identified). Only the survival time differed significantly (L120Q > Y139C = Y139F > susceptible). CONCLUSIONS: Accumulation of chlorophacinone occurs from day 1 to day 4, and an equilibrium is reached, suggesting rapid elimination. Resistant and susceptible rats accumulate chlorophacinone to the same extent and only differ in terms of survival times. Resistant rats may then be a threat for non‐target species for prolonged periods of time. © 2012 Society of Chemical Industry